A Case Study: Multidisciplinary Faculty Members’ Study Abroad Experiences in a Nursing Course (International Journal of Multidisciplinary Perspectives in Higher Education, 2023)
This case study explores the lived experience of three faculty from different disciplines engaged in an experiential undergraduate nursing study abroad (SA) course, which is largely absent from the literature. This research found specific personal and professional transformative effects of multidisciplinary SA experiences for faculty. Considerations for faculty planning to engage in multidisciplinary SA will be identified, including impacts of faculty dynamics and physical and psychological demands. These findings further highlight, document, and contribute to the growing literature related to the experiential impacts of SA on faculty professional development.